Tales from the Ethnographic Field: Navigating Feelings of Guilt and Privilege in the Research Process. Issue 3 (August 2016) - DeLuca, Jaime R.; Maddox, Callie Batts
This article explores questions of reflexivity, positionality, identity, and emotion within the process of ethnographic research. We reflect on our feelings of privilege and guilt in and through our ethnographic fieldwork and discuss the ways in which these experiences encouraged reflexive thinking and a crucial interrogation of the place of the self in the research process. Specifically, we construct individual vignettes centered on our differing research efforts to acknowledge that our work is unavoidably personal and to embrace the myriad ways in which our positionality impacted our findings. We conclude by offering insights into the ways in which our field experiences are important in the production of knowledge, both in our own work and more generally.